Behavioral difficulties and personality traits in childhood - Barkauskienė, Rasa; Kundrotaitė, Gabija; Grauslienė, Izabelė; Gervinskaitė-Paulaitienė, Lina; Čekuolienė, Danguolė; Zbarauskaitė, Asta (Psichologija, 2014)
The destructive behaviors in childhood may have many negative consequences not only for children themselves, but also for their closest social environment and for the wider society. Therefore, the behavior difficulties and conduct disorders in childhood are among the most important focuses of the developmental psychopathology research and practice. Introduction of personality dimensions into this area of investigation is one of the latest routes in these studies. Recently, the Five-factor model, also known as the Big-Five, has been considered to be one of the most compelling perspectives on the personality structure in adults and children. The present study examines multiple links among behavior difficulties and personality traits in children. Another important focus of the present study is on investigating the specific constellations of personality traits that are more likely to manifest with respect to certain patterns of behavioral difficulties in middle childhood. Data provided by the mothers of 451 children (age, 6 to 11 years) are analyzed in the paper. Children’s behavioral difficulties were measured by the Child Behavior Checklist (CBCL6/18). The Hierarchical Personality Inventory for Children (HiPIC, Mervielde & De Fruyt, 1999) was used for evaluating personality traits. Analysis of the links among behavior problems and personality traits revealed that children who scored higher on externalizing difficulties had lower expressions of Benevolence, Conscientiousness, Imagination, and Emotional stability traits. These results are in accordance with the data obtained by other authors in the field. No correlation between Extraversion and Aggressive Behavior and Rule-breaking behavior was found. The positive correlation between the Emotional Instability dimension and the subscales of behavioral difficulties was discovered – children with higher scores on behavioral difficulties appeared to be more anxious and less self-confident. Four clusters based on personality traits were identified – adaptive, expressive, moderate, and vulnerable. The current study has indicated that children who do not demonstrate behavioral difficulties are more likely to be characterized by the adaptive personality profile with a higher expression of Benevolence, Conscientiousness, Imagination, and Extraversion and the moderate personality lower expression of Emotional Instability traits as well as by the profile with the expressed Benevolence trait which was labelled as the moderate group. In turn, children with behavioural difficulties, more often than expected by chance, may be characterized by the expressive personality profile with the expressed Extraversion and Imagination traits and by the vulnerable personality profile with a high expression of Extraversion and a low one of Benevolence and Conscientiousness traits.
Keywords: children’s personality traits; Five Factor model; behavioral difficulties